Nitro sulfonyl fluorides are a new pharmacophore for the development of antibiotics. Issue 4 (13th June 2018) - Sadlowski, Corinne; Park, Bora; Araujo Borges, Clarissa; Das, Subhamoy; Lucas Kerr, D.; He, Maomao; Han, Hesong; Riley, Lee; Murthy, Niren
Abstract : The development of antibiotics against Gram-negative bacteria is a central problem in drug discovery. Abstract : The development of antibiotics against Gram-negative bacteria is a central problem in drug discovery. In this report, we demonstrate that aromatic sulfonyl fluorides with a nitro group in their ortho position have remarkable antibacterial activity and are active against drug-resistant pathogens, such as methicillin-resistant Staphylococcus aureus (MRSA), multidrug resistant Acinetobacter baumannii, and Pseudomonas aeruginosa .